2014
DOI: 10.1149/2.030406jes
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Rich Composition of Li2RuO3and Li2Ru1-xIrxO3Layered Materials as Li-Ion Battery Cathode

Abstract: Li 2 MO 3 -based layered structures play an important role in lithium rich composites to realize high energy density cathode for lithiumion batteries. However, detailed storage mechanism in lithium rich composition is still not clear due to complicated redox chemistry and their synergy effect. In the present work, we report electrochemical property of Li 2 RuO 3 and Li 2 IrO 3 and their solid solution Li 2 Ru 1-x Ir x O 3 (0 ≤ x ≤ 1). Despite having the same structure they differ in space group (C2/c for Li 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…22 However, the electrochemical properties upon cycling under various voltage ranges have not been sufficiently studied for Li 2 RuO 3 and its related solid solutions. 14,[25][26][27][28] Evaluating the electrochemical properties under various (dis)charge voltage ranges is crucial to obtain design guidelines on how to optimize the performance of electrode materials. In this study, the electrochemical properties upon cycling under various charge cut-off voltages and the phase transition behaviors in the initial and second cycles are investigated for Li 2 RuO 3 and Li 2 Mn 0.4 Ru 0.6 O 3 (x = 0.6; hereafter denoted as LMR) showing the largest capacity and good cyclability among Li 2 Mn 1¹x Ru x O 3 system and their relationship to local structure change are discussed.…”
Section: /Rumentioning
confidence: 99%
“…22 However, the electrochemical properties upon cycling under various voltage ranges have not been sufficiently studied for Li 2 RuO 3 and its related solid solutions. 14,[25][26][27][28] Evaluating the electrochemical properties under various (dis)charge voltage ranges is crucial to obtain design guidelines on how to optimize the performance of electrode materials. In this study, the electrochemical properties upon cycling under various charge cut-off voltages and the phase transition behaviors in the initial and second cycles are investigated for Li 2 RuO 3 and Li 2 Mn 0.4 Ru 0.6 O 3 (x = 0.6; hereafter denoted as LMR) showing the largest capacity and good cyclability among Li 2 Mn 1¹x Ru x O 3 system and their relationship to local structure change are discussed.…”
Section: /Rumentioning
confidence: 99%
“…109,110 It has recently been reported that Li 2 MO 3 containing two types of TM elements with different oxidation states (ex: Li 2 M1 3+ M2 5+ O 3 ) is electrochemically active and exhibits interesting properties. 29,111,112 Among these LLCs, Li 4 FeSbO 6 offered a more detailed understanding of the oxygen participation during redox reactions. 30,113 Based on the variation of the redox behavior depending on cutoff voltages (Figure 21a), the authors determined that there are three types of redox centers: reversible redox reactions of TMs (Fe 3+ /Fe 4+ ), Fe 4+ and O 2 n− , respectively.…”
Section: Llcs Containing Heavy Atomsmentioning
confidence: 99%
“…Doping the oxide lattice has demonstrated to be a more facile way to modify the structural properties and to improve the cycling stability/voltage maintenance of LROs. To date, several attempts based on single cation doping have been reported . For example, the Mitra group demonstrated the capacity and cycling stability of LRO were enhanced by introducing an Ir dopant .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several attempts based on single cation doping have been reported . For example, the Mitra group demonstrated the capacity and cycling stability of LRO were enhanced by introducing an Ir dopant . The Im group discovered the Ti 4+ doping led to the improved cycle stability and rate performance of LROs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation